Genome Mapping and Genomics in Fishes and Aquatic Animals - Kocher, Thomas D.; Kole, Chittaranjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
Mapping of animal genomes has generated huge databases and several new concepts and strategies, which are useful to elucidate origin, evolution and phylogeny. Genetic and physical maps of genomes further provide precise details on chromosomal location, function, expression and regulation of academically and economically important genes. The series Genome Mapping and Genomics in Animals provides comprehensive and up-to-date reviews on genomic research on a large variety of selected animal systems, contributed by leading scientists from around the world. This volume summarizes the first era of genomic studies of aquaculture species, in which the tools and resources necessary to support whole-genome sequencing were developed. These tools will enhance efforts toward selective breeding of aquaculture species. Included in this volume are summaries of work on salmonids, cyprinids, catfish, tilapias, European sea bass, Japanese flounder, shrimps and oysters.
Salmonids -- Cyprinids -- Catfish -- Tilapias -- European Sea Bass -- Japanese Flounder -- Shrimp -- Oysters.
Keywords: Animal genetics; Wildlife; Fish; Aquatic ecology .; Genetic engineering; Nutrition .; Animal Genetics and Genomics; Fish & Wildlife Biology & Management; Freshwater & Marine Ecology; Genetic Engineering; Nutrition